Akta Perdamaian Oleh Notaris Sebagai Mediator Alternatif Penyelesaian Sengketa Di Luar Pengadilan - Panjaitan, Wijaya Natalia (Postgraduate Program Doctoral in Law, Universitas Pattimura, 2022)
Introduction: Deed of Peace by a Notary is one of the authority by the Attributive for Notary. This is one of the notary's active roles to act to resolve disputes outside the court. Purposes of the Research: The purpose of this study is to find out how the authority of a Notary as an Mediators in Alternative Dispute Resolution to make a dedd of peace and how the legal force of a peace deed as an alternative dispute resolution outside court. Methods of the Research: This study case uses a normative juridical method by using a statutory and conceptual approach. Results Originality of the Research: Notary has the authority to make a Deed of Peace and act as Mediator in Alternative dispute resolution outside the court which has the same legal force as a court decision if it is registered with the court so it has executorial power.